Asian ethical urbanism : a radical postmodern perspective - Lim, William Siew Wai, 1932-2023 (World Scientific Pub., 2005)
With the impending demise of modernist planning, the footprints and corpses of failed modernist visions are littered everywhere. A vacuum of implementable urban theories has occurred at the time when unprecedented expansion and restructuring of cities in rapidly developing economies are taking place. In this collection of essays, William S W Lim zeroes in on the peculiarities and dynamics of present Asian urban and architectural conditions in order to challenge and transcend the socio-ecological forms and political influences generated by the current system of global capitalism. Part I of this.